Predicting Mechanical Ventilation, Intensive Care Unit Admission, and Mortality in COVID-19 Patients: Comparison of Seven Different Scoring Systems - Tuba İlgar; Sudem Mahmutoğlu Çolak; Kübra Akyüz; Gülsün Çakır Odabaş; Süleyman Koç; Aybegüm Özşahin; Ayça Telatar; Özcan Yavaşi (Türk Yoğun Bakim Derneği Dergisi)
Objective: In this study, we investigated whether scoring systems determine COVID- 19 severity. Materials and Methods: COVID-19 patients hospitalized between 01.09.2020 and 31.04.2021 were retrospectively assessed. The National Early Warning Score (NEWS), Modified Early Warning Score (MEWS), Rapid Emergency Medicine Score (REMS), Quick Sequential Organ Failure Assessment Score (q-SOFA), CURB-65, MuLBSTA, and ISARIC 4C scores on admission day were calculated. Scoring systems’ ability to predict mechanical ventilation (MV) need, intensive care unit (ICU) admission, and 30-day mortality were assessed. Results: A total of 292 patients were included; 137 (46.9%) were female, and the mean age was 62.5±15.4 years. 69 (23.6%) patients required ICU admission, 45 (15.4%) needed MV, and 49 (16.8%) died within 30 days. No relationship was found between qSOFA and MV need (p=0.167), but a statistically significant relationship was found between other scoring systems and MV need, ICU admission, and 30-day mortality (p<0.05). ISARIC-4C (optimal cut-off >5.5) and NEWS (optimal cut-off >3.5) had the highest area under the curve in ROC curve analyses, whereas qSOFA had the lowest. Conclusion: The severity of COVID-19 could be estimated by using these scoring systems, especially ISARIC-4C and NEWS, at the first admission. Thus, mortality and morbidity would be reduced by making the necessary interventions earlier.